Crisis Communication During the Corona Virus 2019 Pandemic via the Ministry of Public Health’s “Thai Roo Soo COVID” Facebook Page - Prasongmongkol, Nisapat; Sridee, Supaporn; Boobsiri, Kan; Ngamsanit, Samarn (Arts of Management Journal, 2023)
This study investigated the Ministry of Public Health’s crisis communication during the COVID-19 pandemic via the “Thai Roo Soo COVID” Facebook page in terms of policies, management, strategies, and approaches for improvement. Data were collected by interviewing 23 people from 4 groups: (1) policymakers, (2) epidemiologists, (3) communications workers, and (4) crisis communication experts. The results showed that: 1) the policy was driven by administrators and emphasized having a risk communication and public relations working team that used mixed media to aggressively communicate beneficial messages to the public with consistent and uniform content. 2) The management structure was based on clearly specified roles and responsibilities for people in each position and allocating sufficient budget, materials, and equipment, as well as coordinating with allied network partners in every sector to join forces in the fight against COVID. 3) The main strategies were to use two-way communication via multiple platforms to respond to the crisis, reach target groups, transmit messages in a way that matches public demand, and inform the public, create understanding, and give people information they could put into practice. 4) The approach for improvement was to use what was learned from the COVID-19 crisis communication experience to prepare for other emergencies or disease outbreaks in the future.